2023
DOI: 10.1155/2023/1014666
|View full text |Cite
|
Sign up to set email alerts
|

Tuberculosis Knowledge, Attitudes, and Practice in Middle- and Low-Income Countries: A Systematic Review

Abstract: Tuberculosis (TB) is the leading cause of death from an infectious agent in the world. Most tuberculosis cases are concentrated in low- and middle-income countries. The aim of this study is to better understand tuberculosis-related knowledge about TB disease, prevention, treatment and sources of information, attitudes towards TB patients and their stigmatization and prevention, diagnosis and treatment practices in the general population of middle- and low-income countries, with a high tuberculosis burden, and … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
1
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(3 citation statements)
references
References 47 publications
0
1
0
Order By: Relevance
“…Past delays in transferring new tools from high-income countries capable of affording them to less economically developed countries have several explanations: problems with local registration, 1 10 11 need for testing locally, [12][13][14] lack of endorsement by entities such as WHO, 1 5 15 16 high price, [17][18][19] constraints in procurement and supply management, 5 20 21 limited manufacturing capacity, 4 22 23 as well as lack of awareness and false perceptions on potential adverse reactions and other complications. 24 25 Therefore, engaging key stakeholders from the first step of designing a clinical trial may facilitate and accelerate the future uptake of new TB regimens in any country, especially the low-income and middle-income countries (LMICs) with high TB burden. While these principles emerge clearly from R&D efforts in TB, rapid implementation of innovations is a general concern to be addressed for any high-burden disease.…”
Section: Bmj Global Healthmentioning
confidence: 99%
“…Past delays in transferring new tools from high-income countries capable of affording them to less economically developed countries have several explanations: problems with local registration, 1 10 11 need for testing locally, [12][13][14] lack of endorsement by entities such as WHO, 1 5 15 16 high price, [17][18][19] constraints in procurement and supply management, 5 20 21 limited manufacturing capacity, 4 22 23 as well as lack of awareness and false perceptions on potential adverse reactions and other complications. 24 25 Therefore, engaging key stakeholders from the first step of designing a clinical trial may facilitate and accelerate the future uptake of new TB regimens in any country, especially the low-income and middle-income countries (LMICs) with high TB burden. While these principles emerge clearly from R&D efforts in TB, rapid implementation of innovations is a general concern to be addressed for any high-burden disease.…”
Section: Bmj Global Healthmentioning
confidence: 99%
“…In 2014 and 2015, all Member States of WHO and the United Nations (UN) committed to ending the TB epidemic, through their adoption of WHO's End TB Strategy and the UN Sustainable Development Goals (SDGs), a key component of which is comprehensive patient-centred care and prevention. Previous studies have shown that knowledge of the core knowledge of TB prevention and treatment has a positive impact on the treatment outcome of TB patients, 2 and improving the level of knowledge of the core knowledge of TB prevention and treatment can effectively avoid the occurrence of delayed diagnosis, thus achieving early detection of active TB patients, and targeting the prevention and treatment of TB. Numerous studies have been conducted on the awareness of core knowledge about TB prevention and control in patients with tuberculosis in treatment, [3][4][5] but few studies have been conducted on patients with tuberculosis who have completed treatment.…”
Section: Introductionmentioning
confidence: 99%
“…The symptoms of TB range from a persistent cough and chest pain to weight loss, fatigue, and fever (Peirse and Houston, 2017;Field et al, 2018;Long et al, 2020). Despite being treatable with antibiotics, challenges such as drug-resistant strains and societal stigmas surrounding the disease continue to complicate efforts to control its spread (Bashorun et al, 2020;Craciun et al, 2023).…”
Section: Introductionmentioning
confidence: 99%